THE MEANING OF MATURITY IN MARRIAGE FROM THE PERSPECTIVE OF ISLAMIC LAW - Ane Fany Novitasari; Thohir Luth; Djumikasih; Nur Chanifah (RADJA PUBLIKA, 2023)
Marriage maturity is intended to build an adult household, although textually it is not stipulated regarding maturity in marriage does not mean that Muslims are free to marry freely without considering their level of maturity. This study aims to examine the meaning of maturity in marriage from the perspective of Islamic law. This research is a normative legal research with a philosophical approach (philosophical approach), statutory approach (statute approach), and conceptual approach (conceptual approach). The techniques for analyzing legal material are survey, question, read, recite/recal, review using a deductive way of thinking. The results of the study show that maturity according to Islamic law is that marriage is carried out within the limits of someone who has entered the baligh phase. The household needs to be built on the basis of maturity so as to give rise to the psychological maturity of each partner, whether husband or wife. Islamic law requires that people who want to marry are truly people who are mentally, physically and psychologically ready, mature and understand the meaning of marriage which is part of worship. The household needs to be built on the basis of maturity so as to give rise to the psychological maturity of each partner, whether husband or wife. Islamic law requires that people who want to marry are truly people who are mentally, physically and psychologically ready, mature and understand the meaning of marriage which is part of worship. The household needs to be built on the basis of maturity so as to give rise to the psychological maturity of each partner, whether husband or wife. Islamic law requires that people who want to marry are truly people who are mentally, physically and psychologically ready, mature and understand the meaning of marriage which is part of worship.